Polystyrene microplastics induce gut microbiome and metabolome changes in Javanese Medaka fish Oryzias javanicus Bleeker, 1854 - Usman, Sunusi; Abdull Razis, Ahmad Faizal; Shaari, Khozirah; Azmai, Mohammad Noor Amal; Saad, Mohd Zamri; Isa, Nurulfiza M.; Nazarudin, Muhammad Farhan (Elsevier Inc., 2022)
Microplastics (MPs) have become emerging pollutants of public health concern, due to their impact on aqua-terrestrial ecosystems and integration into the food web, with evidence of human exposure and unrevealed health implications. There is a paucity of information regarding the effects of MPs exposure on the gut system using metagenomic and metabolomic approaches. In this study, Javanese medaka fish was exposed to 5 µm beads of polystyrene microplastics (PS-MPs) suspensions, at concentrations of 100 μg/L (MP-LOW), 500 μg/L (MP-MED), and 1000 μg/L (MP-HIGH), for a duration of 21 days, and evaluated for gut microbiome and metabolome responses. The results revealed a significant reduction (p < 0.05) in richness and diversity of the gut microbiome in the MP-HIGH group, and identification of 7 bacterial genera as differential features by the Linear discriminant analysis Effect Size (LEfSe). The gut metabolic profile revealed upregulation of 9 metabolites related to energy metabolism, via tricarboxylic acid cycle (TCA), creatine pathway, and urea cycle, as determined by the pathway analysis. Furthermore, positive correlation was found between the genus Aeromonas and glucose, lactate, and creatine metabolites. The study revealed that PS-MPs exposure resulted in altered bacterial microbiome and metabolic disorder related to energy metabolism. It further provided additional data on gut bacterial genera and metabolites associated with MPs toxicity in aquatic organism, which will inevitably enable its future health risks assessment in animals and possibly humans.